Three Prime Repair Exonuclease 1 (TREX1) expression correlates with cervical cancer cells growth in vitro and disease progression in vivo - Prati, Bruna (2019)
Alterations in specific DNA damage repair mechanisms in the presence of human papillomavirus (HPV) infection have been described in different experimental models. However, the global effect of HPV on the expression of genes involved in these pathways has not been analyzed in detail. In the present study, we compared the expression profile of 135 genes involved in DNA damage repair among primary human keratinocytes (PHK), HPV-positive (SiHa and HeLa) and HPV-negative (C33A) cervical cancer derived cell lines. We identified 9 genes which expression pattern distinguishes HPV-positive tumor cell lines from C33A. Moreover, we observed that Three Prime Repair Exonuclease 1 (TREX1) expression is upregulated exclusively in HPV-transformed cell lines and PHK expressing HPV16 E6 and E7 oncogenes. We demonstrated that TREX1 silencing greatly affects tumor cells clonogenic and anchorage independent growth potential. We showed that this effect is associated with p53 upregulation, accumulation of subG1 cells, and requires the expression of E7 from high-risk HPV types. Finally, we observed an increase in TREX1 levels in precancerous lesions, squamous carcinomas and adenocarcinomas clinical samples. Altogether, our results indicate that TREX1 upregulation is important for cervical tumor cells growth and may contribute with tumor establishment and progression.